Optimization of Production of A350 Aircraft Wing Components With Interpretive Structural Modeling Diagram at PT XYZ - Hassan Rahmatillah; Yekti Condro Winursito (International Journal of Mechanical, Industrial and Control Systems Engineering, 2024)
PT XYZ, which aims to optimize the production process of Airbus A350 aircraft wing components. The background of this research focuses on the importance of efficiency and effectiveness in the aviation industry, where each component must be produced to high standards to ensure aircraft safety and performance. In order to achieve this goal, the author applies several methods for completing the task, including system modeling and Interpretive Structural Modeling (ISM). This method allows for in-depth analysis of the structure and relationships between elements in the production system. Data processing is carried out through four main stages: model concept design, data collection, analysis, and evaluation. The raw data used includes the company layout and wing component production flow. The results of this data processing provide significant insights into potential improvements in the existing production system, as well as recommendations for improving operational efficiency. Thus, this report not only contributes to the development of knowledge in the field of systems engineering, but also provides practical advice for PT XYZ to improve their production performance.